1973
DOI: 10.1029/ja078i007p01225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atomic oxygen on the N2vibrational temperature in the lower thermosphere

Abstract: The relative significance of different physical processes that determine the state of vibrational excitation of the molecular constituents in the lower thermosphere has recently been discussed by Bauer et al. [1971]. Walker et al. [1969] have performed detailed calculations of the vibrational temperature of N• in this region under both normal and disturbed atmospheric conditions. Results of a similar nature are described by Bauer et al. [1971] and Kummler and Bortner [1972] and are based on a theoretical inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The laboratory work of Holland [1969] and Ajello [1970] is consistent with all of the molecules initially being in the v"= 0 state. A Boltzmann ground state distribution with a 900øK vibrational temperature, which is consistent with published values [Breig et al, 1973], would change the level populations by less than 10%. This would be insufficient to produce the observed effect.…”
Section: Cartwright [1978] Has Suggested That A' •;U----} A•h• Cas-supporting
confidence: 89%
“…The laboratory work of Holland [1969] and Ajello [1970] is consistent with all of the molecules initially being in the v"= 0 state. A Boltzmann ground state distribution with a 900øK vibrational temperature, which is consistent with published values [Breig et al, 1973], would change the level populations by less than 10%. This would be insufficient to produce the observed effect.…”
Section: Cartwright [1978] Has Suggested That A' •;U----} A•h• Cas-supporting
confidence: 89%
“…The vibrational population of E region N,(X•2;g+), an atmospheric parameter heretofore not investigated in situ, is of aeronomic interest for its role in the energy partition of the atmosphere and in an increasing number of known atmospheric processes [Kummler and Bortner, 1972]. The generally slow nature of the reactions in which vibrational quanta are lost from the homonuclear infrared inactive nitrogen molecule has resulted in several [Walker eta/., 1969;Varnum, 1972;Breig et al, 1973;Jamshidi et al, 1973] recent estimates that nitrogen vibrational temperature may significantly exceed the kinetic temperature at altitudes greater than 100 km. Aeronomically important known production and loss processes for vibrationally excited N, and N,* are summarized in Table 1.…”
Section: Thermospheric N Vibrational Energy Exchange Processesmentioning
confidence: 99%
“…Thus it is necessary to know the distribution of vibrational energy of N• in order to specify precisely the rate for the O + + N• reaction. Several theoretical studies of the vibrational temperature and its diurnal variation resulting from chemical reactions and photoelectron collisions in the mid-latitude ionosphere have been made [Walker, 1968;Walker et al, 1969;Kummler and Bonner, 1972;Varnum, 1972;Breig et al, 1973]. Schunk and Hays [1971] studied the response to auroral precipitation of N• vibration in the lower thermosphere, and Schunk and Banks [1975] have suggested that vibrationally excited N• may be transported from the auroral oval to lower latitudes to produce the mid-latitude F region electron trough.…”
Section: Introductionmentioning
confidence: 99%